Shear strength of a natural and compacted tropical soil - Fagundes, Lucas Savio [UNESP]; Rodrigues, Roger Augusto [UNESP] (My University, 2015)
Tropical soils have peculiar characteristics and behavior due to its geology and soil-forming processes typical of tropical regions. Besides the mineralogical composition and complex structures, long periods of rainy and dry seasons, which is common in tropical areas, leads the soil to an unsaturated condition. These factors can significantly influence the geotechnical soil properties. This paper presents the shear strength study of a saturated and unsaturated lateritic tropical soil, via triaxial compression tests on undisturbed (loose) and compacted soil samples. The shear strength of the soil increases hyperbolically with increasing suction for both undisturbed and compacted soils. The variation of shear strength with increasing suction for the compacted soil is much greater than the variation for the undisturbed soil. It indicates that the benefits of compaction, as a soil-improving practice, can be more advantageous for unsaturated soils.
Keywords: shear strength; soil suction; undisturbed and compacted soil; unsaturated and saturated soil